A good place for bringing up children? Mother's neighbourhood perceptions and children's behavioural development in the Millennium Cohort Study. (13th September 2011) - Scheiwe, A; Kelly, Y; Stafford, M; Watt, R
Abstract : Background: Ecological models of early child development postulate that safe and cohesive neighbourhoods are important for healthy development. However, research from the UK on associations between neighbourhood social characteristics and young children's behavioural outcomes is sparse and has yielded inconsistent results. Aim: To explore the associations between persistent low satisfaction with the neighbourhood social environment, as reported by the mother, and children's behavioural development. Design: Secondary analysis of longitudinal data from the Millennium Cohort Study. Setting: United Kingdom. Participants: 8526 mother and child pairs for whom information was complete across all four sweeps. Main outcome measure: Behavioural and emotional difficulties at sweep 4 (age 7), measured via the Strengths and Difficulties Questionnaire (SDQ). Methods: Perceptions of the neighbourhood social environment were measured at sweeps 1–3. Items were combined to derive a 'neighbourhood satisfaction' score. A dummy variable was created to differentiate between families who perceived their neighbourhood social environment as poor either never (reference category), at one sweep, at two sweeps or at three consecutive sweeps. The associations between low neighbourhood satisfaction across sweeps and children's behavioural and emotional difficulties were tested via multiple linear regression. Results: We found a linear relationship between exposure to perceived adverse neighbourhood conditions across sweeps 1–3 and children's behavioural and emotional difficulties at sweep 4 (age 7). The relationship was attenuated but remained statistically significant after individual characteristics, family socio-economic factors and indicators of maternal psychological distress were accounted for. The sample mean for behavioural and emotional difficulties was 7.7 on the Total Difficulties Scale. In the fully adjusted model, low neighbourhood satisfaction at one sweep was associated with an average increase of 0.7 points (95% CI 0.38 to 1.08), for low satisfaction at two sweeps this was 0.9 (95% CI 0.41 to 1.32) and for low satisfaction at all three sweeps the increase was 1.0 (95% CI 0.43 to 1.62), compared to the reference category. Conclusions: The results suggest that children's behavioural development is affected by maternal perceptions of the neighbourhood over and above individual socio-economic factors. Persistent exposure to perceived adverse neighbourhood conditions had the most detrimental effect, supporting a cumulative effect hypothesis. Part of the association appears to be mediated by the psychological well being of the mother. Policy interventions aiming to improve children's behavioural development should take the neighbourhood social environment into account.